Peroneal nerve palsy due to rare reasons: a report of three cases - Yilmaz, Erhan; Karakurt, Lokman; Serin, Erhan; Güzel, Hikmet (My University, 2004)
Peroneal nerve entrapment was diagnosed in three patients (2 males, 1 female) by clinical and electrophysiological studies. Of these, one patient had postural bilateral involvement due to prolonged squatting, while two patients had mechanically-induced entrapment. Initially, all the patients were treated conservatively with a drop-foot splint and vitamin B. One patient responded to treatment; in one patient with bilateral involvement, right-sided peroneal nerve palsy improved. Upon detection of no clinical and electrophysiological improvement after three months of conservative treatment, surgical decompression was performed in two patients, which resulted in a successful outcome in the patient with bilateral palsy. Incomplete recovery was obtained in the other patient with diabetic polyneuropathy.
Uç olguda nadir nedenlerle oluşan peroneal sinir felci.
Keywords: Adult; Decompression, Surgical; Diagnosis, Differential; Electromyography; Female; Humans; Male; Nerve Compression Syndromes; Peroneal Neuropathies; adult; article; case report; decompression surgery; differential diagnosis; electromyography; female; human; male; nerve compression; pathology; peroneal neuropathy